2013
DOI: 10.1186/1472-6963-13-211
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of routine collection of patient reported outcome measures on patients, providers and health organisations in an oncologic setting

Abstract: BackgroundDespite growing interest and urges by leading experts for the routine collection of patient reported outcome (PRO) measures in all general care patients, and in particular cancer patients, there has not been an updated comprehensive review of the evidence regarding the impact of adopting such a strategy on patients, service providers and organisations in an oncologic setting.MethodsBased on a critical analysis of the three most recent systematic reviews, the current systematic review developed a six-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
587
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 668 publications
(602 citation statements)
references
References 61 publications
10
587
0
5
Order By: Relevance
“…35,59 The integration of PROs in clinical work flow and its uptake in routine clinical care for management of patients is still in its infancy and little research attention has focused on key success factors of implementation of PROs in clinical care to as recommended by Greenhalgh and colleagues. 60 Our experience in Ontario, Canada supports the need for multifaceted implementation strategies that are tailored based on identified barriers in clinical care and use of change management coaching for facilitating uptake of PROs in the clinical encounter that are Accepted Article 20 informed by knowledge translation approaches. 61 Clinician attitudes that nothing can be done to change fatigue or sleep disturbances in the context of cancer treatment may influence the value they place on usefulness of this data in clinical care.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…35,59 The integration of PROs in clinical work flow and its uptake in routine clinical care for management of patients is still in its infancy and little research attention has focused on key success factors of implementation of PROs in clinical care to as recommended by Greenhalgh and colleagues. 60 Our experience in Ontario, Canada supports the need for multifaceted implementation strategies that are tailored based on identified barriers in clinical care and use of change management coaching for facilitating uptake of PROs in the clinical encounter that are Accepted Article 20 informed by knowledge translation approaches. 61 Clinician attitudes that nothing can be done to change fatigue or sleep disturbances in the context of cancer treatment may influence the value they place on usefulness of this data in clinical care.…”
Section: Discussionmentioning
confidence: 80%
“…A number of systematic reviews have shown that feedback of PROMs data to clinicians may improve communication and the attention paid to symptoms but the effects on health outcomes remains uncertain. 60,61 This lack of an effect has been explained by the lack of attention paid to the complex processes involved to ensure integration of PROMs data in the clinical encounter and for use in clinical decision-making. 64 Attention to the use of knowledge translation Accepted Article 22 theories and strategies in the implementation and uptake of PROMs in clinical practice has been advised.…”
Section: Discussionmentioning
confidence: 99%
“…There are 16 reviews of the quantitative/randomised controlled trial (RCT) literature on the feedback of individual-level PROMs data 24,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] and one review currently in progress. 57 There is also one review of qualitative studies 58 and four mixed-method reviews.…”
Section: Existing Evidencementioning
confidence: 99%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk oncology settings, 42,43,46,55 one review focused on use of PROMs as a means of screening for cancer-related distress 56 and two reviews focused on the use of PROMs feedback in palliative care settings. 59,60 One review focused on feedback of PROMs data to allied health professionals.…”
Section: Introduction and Overviewmentioning
confidence: 99%
See 1 more Smart Citation